The Influence Of Beauty Influencers, Lifestyle, And Halal Label On The Purchase Decision Of Somethinc Cushion Product - Fadilla, Dina; Sitepu, Novi Indriyani; Sari, Nurma; Nurlina, Eka; Syukri, Sarah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study analyzes the effect of Beauty influencers, Lifestyle, and Halal labels on purchasing Cushion Somethinc products. This study uses a quantitative method using a Likert scale. The sample for this study were students of the Faculty of Economics and Business at Syiah Kuala University who used the Cushion Somethinc product. 110 respondents were taken through purposive sampling using the Hair formula. The analytical method used is multiple regression analysis. The results of this study indicate that Beauty Influencer, Lifestyle, and the Halal Label have a positive and significant effect on the decision to buy cushion Somethink products. Beauty influencers are helpful for brands wishing to adopt the marketing strategy for developing local cosmetic products and making lifestyle and halal labels an indicator in purchasing decisions.